Manual de procedimentos de aplicação de sanções administrativas aos fornecedores: uma contribuição à seção de cadastro de empresas da Universidade Federal da Paraíba - Catanduba, Laryssa Brilhante (2021)
In the context of budgetary execution, more specifically in the bidding, contracting and contractual execution phases, it may be necessary to carry out administrative procedures to investigate infractions committed by suppliers that are related to the Public Administration. And yet, the legal-administrative regime entails a power-duty for the Public Administration once it is found that the suppliers' obligations under the law, notices, terms of reference and contracts have been breached, proceed with a sanctioning process, respecting the principles of due process legal, contradictory and broad defense. Therefore, the objective of the work is to prepare a proposal for a manual of administrative procedures for the specification and standardization of activities related to the application of solutions to suppliers by the UFPB Company Registration Section. The method of approach used was the deductive, being a research of an applied nature, specialized descriptive, and bibliographic and documentary sources. In this sense, doctrinal elements, legal instruments and guidelines of the control bodies on administrative procedures regarding the execution of public expenditure, biddings, contracts and administrative processes were identified. An analysis of the sanctions application processes carried out by the UFPB Company Registration Section in 2019 and 2020 was carried out, as well as the analysis of manuals prepared by other management bodies. As a final result, a proposal for a manual of procedures was presented for the subsidiary to apply solutions to suppliers. The manual is an important tool to help conduct sanctioning processes, standardize procedures and avoid errors, generating efficiency gains.